THE EFFECT OF ADMINISTRATION OF ETHANOL EXTRACT OF RED GALANGA (Alpinia purpurata K. Schum) RHIZOMES ON THE HISTOPATHOLOGY OF WISTAR RATS BREAST CANCER CELLS INDUCED BY DMBA (7,12-dimetilbenz[a]antrasena) - Wahjuni, S.; Bawa, I G. A. G.; Sawitri, N. M. N. (Jurnal Kimia (Journal of Chemistry); Vol. 19 Issue 2, Juli 2025DO - 10.24843/JCHEM.2025.v19.i02.p05, 2025)
Rimpang lengkuas merah ( Alpinia purpurata K.Schum ) merupakan tanaman yang berpotensi sebagai produk alami. Produk alami ini memiliki aktivitas yang bergantung pada jumlah senyawa aktif yang diekstraksi dan metode ekstraksi. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian suplementasi etanol rimpang lengkuas merah terhadap perubahan histologis kanker payudara. Metode yang digunakan adalah metode skrining fitokimia, identifikasi menggunakan instrumen LC-MS/MS, pemeriksaan histopatologi jaringan kelenjar payudara, DMBA, rotary evaporator vakum, dan seperangkat alat LCMS/MS ACQUITY UPLC®H-Class System (Water, AS). Rimpang lengkuas merah (Alpinia purpurata K.Schum) diperoleh dari Desa Badung dan diidentifikasi di Pusat Konservasi Tumbuhan LIPI-UPT Kebun Raya “Eka Karya” Bali. Rimpang lengkuas merah dengan induksi DMBA pada berbagai dosis menunjukkan bahwa ekstrak etanol rimpang lengkuas merah berpengaruh dalam memperbaiki gambaran histopatologi sel kanker payudara mencit pada dosis 70 mg/kgBB/hari dan 90 mg/kgBB/hari. Kata kunci: Antikanker, kanker payudara, DMBA, histopatologi, rimpang lengkuas merah ABSTRACT      The red galangal rhizomes ( Alpinia purpurata K.Schum ) plant has natural product potential. The Natural product has the activity of a plant, which depends on the amount of active compound extracted and the extraction method. This study aimed to determine the effect of the administration of ethanol on supplementing red galanga rhizomes on histological changes in breast cancer. Using phytochemical screening methods, identification using LC-MS/MS instruments, histopathological examination of breast glandular tissue, DMBA, a Vacum rotary evaporator, a set of tools, and an LC-MS/MS ACQUITY UPLC®H-Class System (Waters, USA). The red galangal rhizome ( Alpinia purpurata K.Schum) was obtained from Badung village and determined at the LIPI-UPT Center for Plant Conservation of the Bali “Eka Karya” Botanical Garden. The red galanga rhizomes reported that the higher the ethanol concentration, the higher the perhexiline content was thought to be anti-breast cance r. Phytosphingosine had the anticancer activity of red galanga rhizomes, with DMBA induction at various doses showing that the ethanol extract of red galangal rhizomes had an effect in improving the histopathological picture of mouse breast cancer cells at doses of 70 mg/ kgBW /day and 90 mg/ kgBW /day. Keywords: Anticancer, breast cancer, DMBA, histopathology, red galanga rhizomes